2019
DOI: 10.1037/vio0000165
|View full text |Cite
|
Sign up to set email alerts
|

Bystander intentions to intervene and previous sexual violence education: A latent class analysis.

Abstract: Objective: Further nuance is required in our efforts to understand how we conceptualize bystander intervention. The purpose of this article is to use person-centered analysis to develop classes of students' intentions to intervene in high-risk and postassault situations, and to determine whether membership in classes is associated with the amount of sexual violence prevention education received. Method: Latent class analysis was performed with a sample of 7,146 undergraduate student survey responses to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Only few studies have conducted LCA on the broad topic of (sexual) violence (Ansara & Hindin, 2010;Cavanaugh et al, 2012;Clarke et al, 2016;French et al, 2014;Lysova & Dim, 2020;Macy et al, 2007;McMahon et al, 2019;Nelon et al, 2019;O'Connor et al, 2021). However, none of them focused on male victims of sexual violence in the general population, but rather focused on (sexual) violence within a sample of high school students, college students and children attending primary school (Clarke et al, 2016;French et al, 2014;Macy et al, 2007;Nelon et al, 2019), intimate partner violence (Ansara & Hindin, 2010;Cavanaugh et al, 2012;Lysova & Dim, 2020) or topics related to sexual violence such as bystander intentions and exposure to sexual violence messages (McMahon et al, 2019;O'Connor et al, 2021). Only one study specifically focused on male victims in the context of intimate partner violence in their ongoing relationship (Lysova & Dim, 2020).…”
Section: Severity Profilesmentioning
confidence: 99%
“…Only few studies have conducted LCA on the broad topic of (sexual) violence (Ansara & Hindin, 2010;Cavanaugh et al, 2012;Clarke et al, 2016;French et al, 2014;Lysova & Dim, 2020;Macy et al, 2007;McMahon et al, 2019;Nelon et al, 2019;O'Connor et al, 2021). However, none of them focused on male victims of sexual violence in the general population, but rather focused on (sexual) violence within a sample of high school students, college students and children attending primary school (Clarke et al, 2016;French et al, 2014;Macy et al, 2007;Nelon et al, 2019), intimate partner violence (Ansara & Hindin, 2010;Cavanaugh et al, 2012;Lysova & Dim, 2020) or topics related to sexual violence such as bystander intentions and exposure to sexual violence messages (McMahon et al, 2019;O'Connor et al, 2021). Only one study specifically focused on male victims in the context of intimate partner violence in their ongoing relationship (Lysova & Dim, 2020).…”
Section: Severity Profilesmentioning
confidence: 99%
“…Findings have shown that a considerable number of cases of VAW occur in the presence of bystanders ( Burn, 2009 ; Gracia et al, 2018 ; European Institute for Gender Equality [EIGE], 2020 ; León et al, 2022 ; Sánchez-Prada et al, 2022 ) and suggest the need and relevance for working with these individuals and convert them into “actionists,” active agents of prevention ( McMahon and Banyard, 2012 ; Fenton and Mott, 2017 ; Fenton et al, 2019 ; McMahon et al, 2019 ; Rothman et al, 2019 ). This leads to the development of intervention programs to modify attitudes and beliefs held by bystanders (such as possible sexist attitudes or blaming the victim) and to strengthen their active responses (reactive and/or proactive) toward the victims ( UNWomen, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the development of intervention programs to modify attitudes and beliefs held by bystanders (such as possible sexist attitudes or blaming the victim) and to strengthen their active responses (reactive and/or proactive) toward the victims ( UNWomen, 2015 ). An important part of these programs, and the research on which they are based, has focused on cases of sexual VAW ( Crooks et al, 2019 ; Kettrey and Marx, 2019 ; McMahon et al, 2019 ; Mainwaring et al, 2022 ; Woods et al, 2022 ), although they have been applied to others forms of VAW, such as IPVAW ( Banyard et al, 2020 ; European Institute for Gender Equality [EIGE], 2020 ; Sprang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations